Functionalised Polyaniline Nanowires: A Prospective Biosensing Platform - Gangopadhyay1, Rupali; Dutta Chowdhury2, Ankan; De2, Amitabha (Asian Journal of Chemistry, 2013)
Polyaniline nanowires (PAn-NW) are considered as promising materials for fabrication of biosensors. In this work we have functionalized polyaniline nanowires for fabrication of a biosensing platform which was exploited for fabrication of two different biosensors. In one of our work we have immobilized single stranded DNA oligonucletide (ssdA) on this platform and have monitored its combination with the complementary strand (ssdT) following cyclic voltammetry (CV), differential pulse voltammetry (DPV) and electrochemical impedance spectroscopy (EIS) techniques. The system works well even at concentrations as low as 10-18 M (of target nucleotide) and produces substantially large peak current (mA) in DPV. In a parallel work we have immobilized glucose oxidase on this platform that could be used for amperometric detection of glucose in aqueous solution over a wide concentration range of 1 μM - 20mM. The biosensor effectively performs a selective electrochemical analysis of glucose with a very low detection limit of 1 μM glucose concentration and exhibits excellent sensitivity of 14.63 μA mM-1 cm-2 in the presence of common interferrants.